2017
DOI: 10.1155/2017/5952149
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of α-Synuclein in Cerebellar Purkinje Cells of Diabetic Rats and Its Potential Relationship with Inflammation and Oxidative Stress Markers

Abstract: Objective. The present study was conducted to evaluate the relationship between plasma oxidative stress markers such as malondialdehyde (MDA) and glutathione (GSH), inflammatory marker pentraxin-3 (PTX3), and cerebellar accumulation of α-synuclein in streptozotocin- (STZ-) induced diabetes model in rats. Methods. Twelve rats were included in the study. Diabetes (n = 6) was induced with a single intraperitoneal injection of streptozotocin (STZ, 60 mg/kg). Diabetes was verified after 48 h by measuring blood gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
(40 reference statements)
1
12
2
Order By: Relevance
“…Consistent with methods used in the previous reports (Nagayach et al, 2014;Razi et al;Sherif, 2017;Solmaz et al, 2017), our study showed that the intraperitoneal administration of STZ caused a clear-cut increase in blood and urine glucose levels, with common signs of diabetes, including body weight loss, polyphagia, polydipsia and polyuria, which was due to the diabetogenic action of STZ, thus inducing the degeneration in pancreatic Langerhans islet beta cells (Akbarzadeh et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with methods used in the previous reports (Nagayach et al, 2014;Razi et al;Sherif, 2017;Solmaz et al, 2017), our study showed that the intraperitoneal administration of STZ caused a clear-cut increase in blood and urine glucose levels, with common signs of diabetes, including body weight loss, polyphagia, polydipsia and polyuria, which was due to the diabetogenic action of STZ, thus inducing the degeneration in pancreatic Langerhans islet beta cells (Akbarzadeh et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Impaired mitochondrial biogenesis, depolarization of mitochondrial membrane potential, and increased reactive oxygen species (ROS) have been reported in neuronal cells with IR [16]. In addition, diabetic rats exhibited increased SNCA in Purkinje cells [17]. Furthermore, several anti-glycemic agents, including exenatide, a glucagon-like peptide analogue, have exerted a disease-modifying effect on PD; exenatide is presently in phase III clinical trial as a neuroprotective drug for patients with PD [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…α-Synuclein is a pre-synaptic protein involved in the regulation of exocytotic vesicles [33,67], and its expression increases in response to brain injury [68]. Further, α-synuclein oligomerization is important in the pathogenesis of synucleinopathies [69,70], where it forms neurotoxic oligomers [70][71][72][73] that accumulate in and damage Purkinje cells [74][75][76]. When released into the extracellular space, α-Synuclein oligomers are potent inducers of neuroinflammatory M1 microglia and A1 astrocyte polarization [77,78].…”
Section: Discussionmentioning
confidence: 99%